KONSEP EPISTEMOLOGI DALAM PEMIKIRAN IBNU RUSYD - Yamin Yamin; Astrid Veranita Indah (Sulesana, 2023)
This study aims to analyze the dimensions of epistemology or philosophy of knowledge in the thought of Ibnu Rusyd, who lived in 520H/1126 AD. There are two theories used to study Ibnu Rushd's epistemological thinking. First, the epistemological classification consisting of 4 forms, namely bayânî, burhâni, irfânî and tajrîbî. Second, Abd Jabbar's theory of plurality of text meanings. Each text contains the possibility of other meanings that are not the same as those explicitly stated. These meanings are always born and differ according to the different approaches and methods used. However, this does not mean that there is an exclusivity of understanding but that the text (al-Qur'an) provides a large space for various understandings according to the level of reasoning.